Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Peter McCawley (Faculty of Economic & Business Universitas Gadjah Mada, 2010)
NO. Penulis --- Judul Artikel --- Halaman 1. Peter McCawley --- Infrastructure Policy in Indonesia : New Directions --- 1-16 2. Meirani Harsasi dan Fahmy Radhi --- The Influence of Implementing Quality Management Towards Purchasing Performance and Competitive Advantage Making --- 17-28 3. Hirwan Hamidi --- The Impact of Contract Farming on the Profit of Virginia Tobacco Farming in Lombok Island, West Nusa Tenggara --- 29-40 4. Daniey Adi Purwanto --- Decentralization and Its Impact on Primary Education Outcomes --- 41-58 5. Prihadi Nugroho --- Reconciling Industrial Clusters and Urban Systems Through Regional Network Governance : A Case of Central Java Province --- 59-76 6. Ridwan Sutriadi --- Financial Crisis Versus Debate on Urban Space, Challenge, and Research Agenda --- 77-100 7. Poerwaningsih S. Legowo --- The Impact of Road Network Linkages for Region Sectoral Growth in JABODETABEK Area --- 103-113 8. Muhammad Firdaus dan Annisa Fitria --- Does the Rank-Size Rule Matter in Indonesia? Determinants of the Size Distribution of Cities --- 114-120